Implementación de una página web para la promoción y gestión de arriendos, en la ciudad de Guaranda, año 2023 - Calvache Hernandez, Juan Fernando (2024)
The purpose of this work is to contribute to the well-being of the community of the State University of Bolívar, which has a significant number of students from other regions. These students often face difficulties in finding accommodation that suits their needs, as so far there are only informal methods of finding housing. To address this problem, we have adopted a development methodology based on prototypes for the creation of a web page. This methodology focuses on continuous feedback from the end user, which has allowed us to refine the final version of the platform through iterations of its functions. During the website development process, we managed to create a platform with a scalable architecture and easy maintenance at the software level. This is crucial given that the real estate market is constantly changing, and our platform must adapt to new needs and trends. However, one of the most significant achievements was the requirements gathering phase, where we obtained valuable metrics. These metrics allowed us to design forms and search parameters that have been implemented on the website effectively. As a result, a communication channel has been established between tenants and landlords. Both groups have at their disposal a platform where they can advertise and search for apartments in a more comfortable way and according to their individual needs. In conclusion, this initiative has significantly improved the housing search experience for foreign students at the State University of Bolívar, offering an effective and convenient solution. Keywords: property, landlord, tenant, website, rentals.